Clinical utility of denosumab for treatment of bone loss in men and women - Adler R (Dove Medical Press, 2011)
Robert A Adler, Ranjodh S GillEndocrinology and Metabolism, McGuire Veterans Affairs Medical Center, Richmond, VA, USAAbstract: While most older patients with osteoporosis are treated with antiresorptive bisphosphonates such as alendronate, risedronate, ibandronate, and zoledronic acid, such drugs have side effects, remain in bone for extended periods, and lead to poor adherence to chronic treatment. Denosumab is a humanized monoclonal antibody and antiresorptive agent that works by decreasing the activity of the receptor activator of nuclear factor kappa B ligand. In major trials in postmenopausal women, denosumab increased bone mineral density by dual energy x-ray absorptiometry in the spine, hip, and distal third of the radius and decreased vertebral, nonvertebral, and hip fractures. Denosumab is administered by subcutaneous injection every six months, suggesting that adherence may be improved with such therapy. In addition, pharmacokinetic studies measuring bone turnover markers imply that the antiresorptive effect diminishes more quickly over time. Whether these properties will lead to fewer long-term side effects needs to be proven. Denosumab has also been studied in men with prostate cancer treated with androgen deprivation therapy. These men, at high risk for fracture, also have increases in spine, hip, and forearm dual energy x-ray absorptiometry, as well as fewer morphologic vertebral fractures on x-ray. Denosumab is approved for postmenopausal women with osteoporosis in the US and Europe and for men on androgen deprivation therapy in Europe.Keywords: osteoporosis, fracture, denosumab, bisphosphonates, dual energy x-ray absorptiometry, androgen deprivation therapy, osteonecrosis of the jaw